1989
DOI: 10.1103/physrevlett.62.1880
|View full text |Cite
|
Sign up to set email alerts
|

Calorimetric evidence for structural relaxation in amorphous silicon

Abstract: Differential scanning calorimetry of amorphous silicon ( Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
84
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(89 citation statements)
references
References 16 publications
4
84
1
Order By: Relevance
“…[22][23][24][25] Both the coordination defects and the bond angle distortion depend on the process history of a-Si, since it was widely shown that as-implanted a-Si, if annealed, undergoes a structural relaxation, with a heat release measured by differential scanning calorimetry at temperatures below the onset of crystallization. 26 In the mid nineties, after investigation through Raman spectroscopy, x-ray techniques, and photocarrier lifetime measurements, the origin of this relaxation was attributed to the recombination of the coordination defects, decreasing from $0.5% to 0.05%, and to the reduction of the bond angle distortion, from 12 to 9 . 20,27 Such a process was shown to be reversible, even if with an hysteresis loop, since ion implantation (leading to a damage level larger than $0.1 displacements per atom) performed on relaxed a-Si reproduces the same strain status as in the asimplanted a-Si.…”
Section: A Defects and Diffusion In Amorphous Simentioning
confidence: 99%
“…[22][23][24][25] Both the coordination defects and the bond angle distortion depend on the process history of a-Si, since it was widely shown that as-implanted a-Si, if annealed, undergoes a structural relaxation, with a heat release measured by differential scanning calorimetry at temperatures below the onset of crystallization. 26 In the mid nineties, after investigation through Raman spectroscopy, x-ray techniques, and photocarrier lifetime measurements, the origin of this relaxation was attributed to the recombination of the coordination defects, decreasing from $0.5% to 0.05%, and to the reduction of the bond angle distortion, from 12 to 9 . 20,27 Such a process was shown to be reversible, even if with an hysteresis loop, since ion implantation (leading to a damage level larger than $0.1 displacements per atom) performed on relaxed a-Si reproduces the same strain status as in the asimplanted a-Si.…”
Section: A Defects and Diffusion In Amorphous Simentioning
confidence: 99%
“…23 Experiments have shown that during relaxation, the bond-angle dispersion and the density of point defects diminish. 5,8,12,24,25 This evolution has been simulated by molecular dynamics, too.…”
Section: Microscopic Interpretation Of the Energy Of Relaxation mentioning
confidence: 99%
“…An interesting prediction of our analysis is that the heat of crystallization of a-Si may be lower than the reported values of 11-14 kJ/mol. 23,38,39 If the density of defects were lower, Q cryst could be as low as 6.6 kJ/mol. In fact, the first crystallization experiments of a-Si reported a value of 9.2 kJ/mol.…”
Section: B Crystallizationmentioning
confidence: 99%
“…1(a), arises from the difference in Gibbs energy between hydrogenated amorphous Si (a-Si:H) and crystalline Si. 11 A unique feature of the in-plane growth lies in that the movement of catalyst drops can be guided by simple surface features, like a single edge step. This allows to determine the position and the growth path of the SiNWs 7,8,10,12 and offers an exciting opportunity to position the in-plane SiNWs during their growth without interrupting the vacuum.…”
mentioning
confidence: 99%